The budget execution of the Federal Institute of the North of Minas Gerais — 2012 to 2015 - Duarte, Marluce (Educação, Escola & Sociedade, 2019)
Public budget is a planning instrument that estimates the revenues to be collected, fixes the expenses to be carried out and seeks the effectiveness and cost-effectiveness of the services rendered to society. Its execution, object under study, represents the annual fulfillment of the objectives and goals determined for the public institution in the process of integrated planning and demands the mobilization of human, material and financial resources. Thus, this work was carried out with the objective of analyzing the performance of the budget execution of the Federal Institute of the North of Minas Gerais (IFNMG), during the period of 2012 to 2015. It was sought to analyze the performance of the Institute’s revenues and expenditures; describe the budget profile of its executed expenses. In methodological terms the research, regarding the ends, is characterized as descriptive; media, such as bibliographical and documentary with a quantitative approach. The data were collected using consultations with the Integrated System of Financial Administration of the Federal Government and the Integrated System of Planning and Budget, and the Management Reports. The results show that the expenses with personnel and social charges are those that have more participation in the annual budget of the Institution, followed by expenses of costing and, finally, the investments that are inexpressive in relation to the total of the annual budget. Keywords: Public Administration. Planning and Budget Execution. Public budget.